ANALISIS KESIAPAN REMAJA UNTUK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI DI DESA KAYU ELANG KECAMATAN SEMIDANG ALAS KABUPATEN SELUMA - Nurrahmah, Hestri Azizah; Mariya, Sri (JURNAL BUANA, 2024)
This study aims to determine: (1) The readiness of adolescents to continue their education to tertiary institutions in Kayu Elang Village, Semidang Alas District, Seluma Regency in terms of internal factors, (2) The readiness of adolescents to continue their education to tertiary institutions in Kayu Elang Village, Semidang Alas District, Seluma Regency viewed from external factors. This type of research used is qualitative. As many as 6 teenagers were selected as research informants based on certain criteria. To collect data used the method of observation, interviews, and documentation. The data is then checked for validity through source triangulation. Furthermore, analysis is carried out using data condensation techniques, data presentation, as well as drawing conclusions and verification. The results showed: (1) the readiness of adolescents to continue their education to tertiary institutions in Kayu Elang Village, Semidang Alas District, Seluma Regency, in terms of internal factors, was not ready. (2) the readiness of youth to continue their education to tertiary institutions in Kayu Elang Village, Semidang Alas District, Seluma Regency in terms of external factors was not ready.